Nitrogen application alleviates salt stress by enhancing osmotic balance, ROS scavenging, and photosynthesis of rapeseed seedlings (Brassica napus) - Tian Tian; Jingang Wang; Haijiang Wang; Jing Cui; Xiaoyan Shi; Jianghui Song; Weidi Li; Mingtao Zhong; Yue Qiu; Ting Xu (Plant Signaling & Behavior, 2022)
Nitrogen application could alleviate salt stress on crops, but the specific physiological mechanism is still unclear. Therefore, in this study, a pot experiment was conducted to explore the effects of different application rates of nitrogen (0, 0.15, 0.30, and 0.45 g·kg−1) on the growth parameters, osmotic adjustment, reactive oxygen species scavenging, and photosynthesis of rapeseed seedlings planted in the soils with different concentrations of sodium chloride (1.5, 3.5, 5.5, and 7.5 g·kg−1). The results showed that nitrogen could alleviate the inhibition of salt on rapeseed growth, and improve the antioxidant enzyme activities and the contents of non-enzymatic substances, K+, soluble protein (SP), soluble sugar (SS), and proline. Besides, there was a significant correlation between the indexes of active oxygen scavenging system, osmoregulation system, and photosynthesis. Therefore, applying appropriate amount of nitrogen can promote the growth and development of rapeseed seedlings under salt stress, accelerate the scavenging of reactive oxygen species, maintain osmotic balance, and promote photosynthesis. This study will improve our understanding on the mechanism by which nitrogen application alleviates salt stress to crops.